BORIC ACID, "CARBONIC" ACID, AND N-CONTAINING OXYACIDS IN AQUEOUS SOLUTION: AB INITIO STUDIES OF STRUCTURE, PKA, NMR SHIFTS, AND ISOTOPIC FRACTIONATIONS - Tossell J.A. (My University, 2005)
B(OH)3 and CO2 are acidic species of considerable geochemical importance, yet the microscopic nature of the acid dissociation reactions for these B and C species is not well understood. Quantum mechanical methods have recently been applied to the direct ab initio calculation of pKa values for many organic and inorganic weak acids, but the B and C acids have not yet been considered in detail. In the present study, pKa values are calculated quantum mechanically for the oxyacids B(OH)3, H2CO3 and HNO3, which have experimental first pKa values of 9.2, 6.4 and −1.3, respectively. We calculate the gas-phase reaction free energies at the highly accurate CBS-QB3 ab initio quantum mechanical level and reaction free energies of hydration using a polarizable continuum method.